1999
DOI: 10.1111/j.1745-3984.1999.tb00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Examinees Use a Review Option to Obtain Positively Biased Ability Estimates on a Computerized Adaptive Test?

Abstract: Part of the controversy about allowing examinees to review and change answers to previous items on computerized adaptive tests (CATs) centers on a strategy for obtaining positively biased ability estimates attributed to Wainer (1993) in which examinees intentionally answer items incorrectly before review and to the best of their abilities upon review. Our results, based on both simulated and live testing data, showed that there were instances in which the Wainer strategy yielded inflated ability estimates as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
(22 reference statements)
1
19
0
Order By: Relevance
“…Arguments against review on CATs have focused primarily on added complications in administration and scoring algorithms, decreased validity and precision resulting from the use of clever answer response strategies, and substantial increases in testing time. Although these problems are serious potential obstacles to overcome, evidence from this study and others (e.g., Stocking, 1997, Vispoel et al, 1999 indicates that these problems may not be insurmountable if review opportunities are limited and special efforts are made to streamline CATs for maximum efficiency.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Arguments against review on CATs have focused primarily on added complications in administration and scoring algorithms, decreased validity and precision resulting from the use of clever answer response strategies, and substantial increases in testing time. Although these problems are serious potential obstacles to overcome, evidence from this study and others (e.g., Stocking, 1997, Vispoel et al, 1999 indicates that these problems may not be insurmountable if review opportunities are limited and special efforts are made to streamline CATs for maximum efficiency.…”
Section: Discussionmentioning
confidence: 80%
“…The tests were adaptive within and between blocks, and all tests were terminated at 40 items. The tests were scored using EAP Bayesian methods as previous research had shown that EAP methods were much less susceptible to score distortion resulting from use of the Wainer strategy than were ML methods (Vispoel et al, 1999). After each item was administered, the computer recorded the item sequence number, the item pool number, the item parameters (a, b, and c), the examinee's answer, the correct answer, the examinee's item score (1,0), the examinee's current (EAP) ability estimate, the posterior variance for that ability estimate, and the time spent answering the item.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the use of computer‐based assessments presents some challenges. Previous research indicates that graphical or complex displays (Mazzeo & Harvey, 1988), speededness (Mead & Drasgow, 1993), screen/font size and resolution (Bridgeman, Lennon, & Jackenthal, 2003; Oetjen & Ziefle, 2009), the (in)ability to revise/review previous responses (Revuelta, Ximenez, & Olea, 2003; Vispoel, Rocklin, Wang, & Bleiler, 1999), and familiarity or practice time with computers (Taylor, Kirsch, Jamieson, & Eignor, 1999; Wang, Jiao, Young, Brooks, & Olson, 2008) may all affect student performance on computer‐based assessments. Moreover, full CBT implementation can be difficult due to limited resources at either the national or school level.…”
mentioning
confidence: 99%
“…Two gaming strategies, typically labeled the Wainer and Kingsbury strategies, have been examined in the research literature. When using the Wainer strategy (see Gershon & Bergstrom, 1995;Stocking, 1997;Vispoel, Rocklin, Wang, & Bleiler, 1999;Wainer, 1993), an examinee would intentionally answer all items incorrectly on the first pass and then answer each item to the best of his or her ability upon review. If the items are sufficiently mismatched to the examinee's true proficiency level, he or she may obtain a positively biased proficiency estimate or a spuriously high proficiency estimate resulting from high measurement error.…”
mentioning
confidence: 99%